Economic burden of congenital athymia in the United States for patients receiving supportive care during the first 3 years of life. (1st January 2021) - Collins, Cathleen; Kim-Chang, Julie J.; Hsieh, Elena; Silber, Abigail; O'Hara, Matthew; Kulke, Sarah; Cooper, Megan A.
Abstract: Aims: Congenital athymia is an ultra-rare pediatric condition characterized by the lack of thymus in utero and the naïve T cells critical for infection defense and immune regulation. Patients with congenital athymia receive supportive care to minimize and treat infections, autoimmune phenomena, and autologous graft-versus-host disease (aGVHD) manifestations, but historically, die within the first 3 years of life with supportive care only. We estimated the healthcare resource utilization and economic burden of supportive care over patients' first 3 years of life in the United States. Methods: A medical chart audit by the treating physician was used to collect patient data from birth to age 3 on clinical manifestations associated with congenital athymia (clinical manifestations due to underlying syndromic conditions excluded). Using costs and charges from publicly available sources, the total economic burden of direct medical costs and charges for the first 3 years of life (considered "lifetime" for patients receiving supportive care) and differences in economic burden between patients with higher and lower inpatient hospitalization durations were estimated. Results: All patients ( n = 10) experienced frequent infections and aGVHD manifestations; 40% experienced ≥1 episode of sepsis, and 20% had recurrent sepsis episodes annually. The estimated mean 3-year economic burden per patient was US5, 534, 121 (2020 US dollars). The annual mean inpatient hospitalization duration was 150.6 days. Inpatient room charges accounted for 79% of the economic burden, reflecting the high costs of specialized care settings required to prevent infection, including isolation. Patients with high inpatient utilization ( n = 5; annual mean inpatient hospitalization duration, 289.6 days) had an estimated 3-year economic burden of US9, 926, 229. Limitations: The total economic burden may not be adequately represented due to underestimation of some direct costs or overestimation of others. Conclusions: Current treatment of patients with congenital athymia (supportive care) presents a high economic burden to the healthcare system.